MIB-1 Is a Suitable Marker of Proliferative Activity in Formalin-fixed, Paraffin-embedded Sections of Breast Cancer - Schmitt, Fernando Carlos [UNESP]; Ferreira, Marcia Pitombeira (SAGE Publications, 1995)
To investigate the expression of a marker of cell proliferation (MIB-1) and its puta tive relationship with tumor size, histologic grading, mitotic index, nodal status, estrogen receptor content, p53 immunoreactivity, and ploidy, we studied 40 cases of invasive breast carcinoma in formalin-fixed, paraffin-embedded tissue sections. The MIB-1, estrogen receptor, and p53 were detected using an avidin-biotin-peroxidase method with microwave antigen retrieval. Ploidy was assessed by image analysis. The median value of MIB-1 index was 15.9% and ranged from 5% to 90%. We found a significant and positive relationship among the MIB-1 index and histologic grading, mitotic index, p53 immunoreactivity, and ploidy, and we demonstrated an inverse relationship between the MIB-1 index and estrogen receptor content. These “ results are similar to those reported using Ki-67 in frozen sections from breast car cinomas. Thus, MIB-1 detected in formalin-fixed material with microwave pre treatment looks to be a reliable marker of proliferation in breast carcinomas. Int J Surg Pathol 2(4):287-294, 1995. © 1995, Sage Publications. All rights reserved.
Keywords: breast cancer; Ki-67 antigen; MIB-1